The triumph of provocation - Mackiewicz, Józef (Yale University Press, 2009)
This political treatise examines the history and nature of Communism as it developed in the Soviet Union and in Poland. The author argues that accommodation with the Communists simply helped them to impose their vision of the world and pursue their goal of global domination.
Keywords: Mackiewicz, Józef.; Mackiewicz, Józef; Communism -- Poland.; Poland -- Relations -- Soviet Union.; Soviet Union -- Relations -- Poland.; Poland -- Politics and government -- 1945-1980.; Pologne -- Politique et gouvernement -- 1945-1981.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; HISTORY -- General.; Communism; International relations; Politics and government; Poland; Soviet Union; Communism -- Politics and Government. -- Poland.; 1945-1980